Willingness to pay for cause-related products: the impact of consumer attitudes and elements of a CrM campaign - Kozłowski, Wojciech (Skłonność do płacenia za produkty z atrybutem społecznym: wpływ postaw konsumenckich i elementów kampanii CrM, 2019)
The article presents the results of research, conducted by experiment, on determinants of the effectiveness of cause-related marketing. Their specific objective was to examine the relationship between the attitudes of women and men and the elements of the CrM campaign and the consumers’ willingness to pay more for cause-related products. The results indicate that willingness will be higher for buyers with favorable attitudes towards CrM, accepting altruistic values and for whom the social cause is of great importance. Research also proves that the price effect of the campaign will be greater if the strategy is linked to utilitarian rather than hedonistic products. These findings can assist companies in designing more effective cause-related marketing strategies
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 4, s. 95-107
Keywords: cause-related marketing; willingness-to-pay; effectiveness; marketing ważnej sprawy; skłonność do płacenia; skuteczność